I-Witness poor children a postcolonial criticism of I-Witness? representation of children in poverty - Narvaez, Alyza Joy Ventura 1991-; Feliciano, Rosa Maria T. (2012)
"Children in poverty has been one of the themes in I-Witness documentaries, a weekly television documentary in GMA 7. This study examines the representations of Filipino children in poverty in selected I-witness documentaries: boy pusit, Bakas ng paa, Nanay na si Nene, Buto't Balat ,Ambulansyang de Paa, Uuwi na si Udong, Batang Langoy, and Batang Kalabaw.It attempts to uncover ideologies embedded in the images and language represented by these documentaries. To attain this objective, textual analysis- through the aid of semiotics and discourse analysis - is used to examine the representations of two important constructions, namely childhood and the Third World, that shape the representation of children in poverty in the selected documentaries."
"The study is guided by postcolonial studies and Roland Barthes' concept of mythology. Post colonial studies guide this by as the Western construction and ideologies present in the documentaries are identified and analyzed. The concept of mythology aids in examining certain myths of childhood and Third World poverty which are employed in the selected documentaries. The results of the study show that Western myths on childhood and the Third World are still infused in the narratives of the documentaries. However, results also show that the incorporation of these myths in the documentaries reflects the perceptions of the members of the production teams, especially the host-writers. Therefore, the results clearly recognized the presence of intervention and how this affects the construction of reality of the children in poverty in the selected documentaries."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Poor children -- philippines; Documentary television programs -- Philippines